Recentering the human in the continuums of in/mobility and in/security: Perceptions from two emblematic borders - Kynsilehto, Anitta; Iglesias Ortiz, Angel (Relaciones internacionales (Madrid), 2023)
This paper argues for a need to decenter the state and (re)center the human when exploring mobilities within international relations scholarship. To make this argument we bring together feminist and critical security studies, as well as multidisciplinary insights, to address the encounter between the person on the move and the enforcement of national sovereignty.  This allows us to highlight the continuums of in/security and im/mobility entwined in this encounter. In so doing, we challenge the discipline’s understanding of security that is often conceptualized from the perspective of state security only, despite critiques of such understandings that emanate from and build on different critical approaches. Furthermore, feminist international relations scholarship and feminist security studies in particular have stressed the necessity to examine security and violence as continuums that traverse across sites ranging from the corporeal and intimate to the global and transnational, and which span over time. Combined with mobility studies that focus on migrant trajectories across countries, regions, and continents with periods of chosen or unwanted immobility in between, this body of scholarship helps us understand how border enforcement impacts diversely positioned persons’ lives. Such an exercise is also useful for making visible the intended and unintended consequences of policymaking that is based on state interests only, and one that refuses to acknowledge the human beings who are caught up in these consequences. Methodologically, the paper draws on long-term ethnographic research conducted at the Mexican side of the Mexico-US border and in Morocco. We have brought together insights from our respective research projects to address border externalization and its impact in two different parts of the world, enacted by two different states (the US) and supranational entities (the EU) on their neighbors to the South, likely to be economically and politically less powerful but supposedly similarly sovereign states. The paper is organized as follows: we begin the first section by discussing the key notion of state sovereignty which is enacted at the border and demonstrate how borders of certain states extend far beyond their demarcated territories. This process, conceptualized as externalization of migration management and border control, can be perceived as contradicting the sovereignty of those states subjected to these externalization practices. We then move on to the notion of security and ask the question of whose security is at stake. Here we demonstrate how the enforcement of state security jeopardizes the safety and security of those people on the move who are located in less privileged positions in the global hierarchies of mobility. In the second section, we discuss how the perspectives outlined in the previous section manifest in our two research sites. This section focuses on the continuums of mobility and immobility and those of security and insecurity, and proposes how we could begin addressing the diversely positioned human as a manifold yet full subject.  We argue that International Relations scholarship usually ignores the human altogether or, at best, acknowledges the human in high-level politics drawing on the model based on the theory on rational actorness. Moreover, the analysis of insights gained at our research sites sheds light on the ways in which mobility is unevenly distributed, and how the enactment of mobility is gendered and racialized in complex ways. We conclude the paper by reflecting what these concerns might mean for international relations scholarship at the conjuncture of human im/mobility and security, and for contributing towards mobility justice.